A waterproof breathable membrane and processing method thereof

By using waterproof and breathable films made of polyethylene, alumina and composite compatibilizers in the construction and transportation fields, combined with flash spinning and hot pressing processes, the problem of insufficient waterproof and breathable function in the prior art is solved, and efficient waterproof and breathable performance is achieved.

CN116200875BActive Publication Date: 2025-04-08JIANGSU QINGYUN NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310117598.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-15
Publication Date
2025-04-08
Estimated Expiration
2043-02-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively realize waterproof and breathable functions in the fields of construction and transportation, especially in places where leakage problems are prone to occur, such as curtain walls and underground continuous walls.

Method used

By preparing a waterproof and breathable film composed of polyethylene, alumina and composite compatibilizer, spinning with flash evaporation technology and performing hot pressing and calendering processes, a film with excellent waterproof and breathable properties is formed.

Benefits of technology

It achieves good waterproof and breathable performance under thinner material levels, improves the waterproof performance of structures such as curtain walls and underground continuous walls, while maintaining high breathability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116200875B_ABST
    Figure CN116200875B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of waterproof membranes, and discloses a waterproof breathable membrane and a processing method thereof, which are made of polyethylene, aluminum oxide and a composite compatibilizer; the mass fraction of the aluminum oxide in the waterproof breathable membrane is 0.5-1%; the mass fraction of the composite compatibilizer in the waterproof breathable membrane is 1.2-1.8%; the application utilizes submicron spherical aluminum oxide dispersed between flash vaporized fibers in the tissue structure of the waterproof breathable membrane to play a waterproof function, and plays a buffering function when the waterproof breathable membrane is subjected to force, thereby improving its tensile strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waterproof membranes, in particular to a waterproof breathable membrane and a processing method thereof. Background Art

[0002] Building curtain walls have always been the main decorative means for the exterior walls of public buildings and medium and high-end residential buildings. Although the national standard "Building Curtain Wall" has put forward requirements for the watertight performance of curtain walls, when designing curtain wall structures, designers are still accustomed to considering structural safety and paying attention to structural strength design and calculation, but not paying enough attention to the design of curtain wall rainwater leakage prevention and the necessary measures to be taken, making leakage one of the common problems of building curtain walls, especially in the southern coastal areas with large rainfall and basic wind pressure and frequent typhoons. Curtain wall leakage is more common, causing the insulation layer to fail, indoor walls to produce wet spots, mildew, etc.; and because the on-site water spray test can only be carried out by sampling detection, there may be parts that cannot meet the watertight performance requirements and have not been sampled, and these parts will become leakage hazards. In addition, deformation and sealant debonding during use will also cause leakage in the building curtain wall after a certain period of use. Therefore, when the insulation material in the curtain wall has a certain water absorption, it is very necessary to set a waterproof layer between the curtain wall and the insulation layer.

[0003] In addition, in the past 10 years, with the development of the economy, my country's transportation industry has developed rapidly. The number of stations in cities has gradually increased, causing the country and the people to pay great attention to the related construction issues. In the construction process of the station, the underground continuous wall, as a deep foundation pit enclosure project, has important functions such as retaining soil, anti-seepage, load-bearing and water interception. In actual construction, underground continuous walls often have leakage problems, which reduces the overall project quality. The application of new waterproof and breathable membranes can effectively solve the leakage problem.

[0004] In the field of building and transportation construction technology, the technical pain points of waterproof and breathable have always troubled technicians. How to use a thinner layer of material to achieve this function has always been the direction of technicians' efforts. This application uses flash evaporation technology to prepare a waterproof and breathable membrane to achieve waterproof and breathable functions in the field of building and transportation.

[0005] For example, the prior art application number 201711415464.9 discloses "The present invention provides a PVC automobile waterproof film and a preparation method thereof. The preparation method comprises mixing PVC, a plasticizer and a stabilizer at a first stirring speed for 10-30 seconds to obtain a primary mixture; when the primary mixture is mixed for 180-220 seconds at a second stirring speed, a flame retardant is added to the primary mixture, and then mixing for 300-400 seconds to obtain a remix; the remix is ​​subjected to banburying and calendering to obtain an automobile waterproof film; the flame retardant is a powder flame retardant. The PVC automobile waterproof film formula that uses powder flame retardant instead of liquid flame retardant and reduces the amount of flame retardant is combined with a specific preparation process for adding flame retardant, so that the odor of the prepared PVC automobile waterproof film is greatly reduced and the environmental protection performance is improved. " Although it has certain waterproof properties, its air permeability is relatively poor, which limits its use.

[0006] Based on this, we propose a waterproof and breathable membrane, hoping to solve the shortcomings of the existing technology. Summary of the invention

[0007] 1. Technical issues to be solved

[0008] In view of the deficiencies in the prior art, the present invention provides a waterproof breathable membrane and a processing method thereof.

[0009] (II) Technical solution

[0010] To achieve the above-mentioned purpose, the present invention provides the following technical solutions:

[0011] A waterproof and breathable membrane is made of polyethylene, aluminum oxide and a composite compatibilizer;

[0012] The mass fraction of the aluminum oxide in the waterproof breathable membrane is 0.5-1%;

[0013] The mass fraction of the composite compatibilizer in the waterproof breathable membrane is 1.2-1.8%.

[0014] As a further technical solution, the alumina is submicron spherical alumina.

[0015] As a further technical solution, the particle size of the submicron spherical alumina is 0.2-1 micron.

[0016] As a further technical solution, the preparation method of the composite compatibilizer is:

[0017] 3-5g of maleic acid complex ester and 0.2-0.4g of diisopropylbenzene peroxide are added to 100-110mL of organic solvent in sequence, stirred and dissolved, and then 10-14g of ethylene-vinyl acetate copolymer is added to adjust the temperature to 70-75°C, and stirred for 40 minutes, and then 3-6g of polyethylene is added, and the stirring is continued for 2-3 hours, and then the mixture is dried by rotary evaporation to obtain a mixture;

[0018] The obtained mixed material is added into a twin-screw extruder for melt extrusion granulation to obtain the compatibilizer.

[0019] As a further technical solution: the preparation method of the maleic acid complex ester is:

[0020] Add sodium silicate to deionized water and stir evenly to obtain a sodium silicate solution with a mass fraction of 6-7%;

[0021] Add 8% ammonium nitrate solution by mass to the sodium silicate solution until the pH of the mixed solution reaches 10, stop adding the ammonium nitrate solution, place it in a water bath at 75°C for aging for 2 hours, filter it, wash it until it is neutral, dry it for 20 hours, grind it, and sieve it to obtain a support;

[0022] Heat 100 mL of deionized water to 80° C., then add 6-7 g of zirconium sulfate, stir evenly, then add 15-18 g of the support, continue stirring for 30 min, then evaporate the water to obtain a reaction material, place the reaction material in a resistance furnace, calcine for 40 min, and naturally cool to room temperature to obtain a composite catalyst;

[0023] 20-23 g of maleic acid and 28-30 g of n-butanol are added to 120 mL of toluene, and then 3-4 g of a composite catalyst is added. After reflux reaction for 3 hours, the solvent is removed by reduced pressure distillation to obtain a maleic acid composite ester.

[0024] As a further technical solution, the organic solvent is acetone.

[0025] As a further technical solution, the extrusion temperature of the twin-screw extruder is 165-170°C;

[0026] The screw speed is 50r / min.

[0027] A method for processing a waterproof breathable membrane comprises the following steps:

[0028] (1) Processing of spinning solution

[0029] Dissolving the spinning raw materials polyethylene, aluminum oxide and a composite compatibilizer in a spinning solvent in sequence to obtain a spinning solution;

[0030] The mass fraction of spinning raw materials in the spinning solution is 7-16%;

[0031] (2) Processing of waterproof and breathable membrane

[0032] The spinning solution prepared in step (1) is flash-spun at 190-220° C. to obtain flash fibers, which are then laid onto a web, subjected to a heat pressing process and a calendering process, and finally wound to obtain a waterproof breathable film.

[0033] As a further technical solution: the spinning solvent is selected from one or more combinations of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, unsaturated hydrocarbons, halogenated hydrocarbons, alcohols, esters, ethers, and fluorocarbons;

[0034] As a further technical solution: the temperature of the hot pressing process is 105-110°C;

[0035] The temperature of the calendering process is 110-120°C.

[0036] (III) Beneficial effects

[0037] Compared with the prior art, the present invention provides a waterproof breathable membrane with the following beneficial effects: the present application utilizes submicron spherical alumina dispersed between flash-evaporated fibers in the waterproof breathable membrane structure to achieve a waterproof function, and also plays a buffering function when the waterproof breathable membrane is subjected to stress, thereby improving its tensile strength.

[0038] Submicron spherical alumina is directly dispersed in the waterproof breathable membrane system. Since the interface compatibility between submicron spherical alumina and polyethylene is relatively low, the dispersibility of submicron spherical alumina in the waterproof breathable membrane system will be reduced, and it is easy to cause multiple aggregation points of submicron spherical alumina, which affects the performance of the waterproof breathable membrane. Therefore, the present invention introduces a certain amount of composite compatibilizer. When the polyethylene resin is subjected to high temperature and strong shear stress, part of the polyethylene C-H bonds or C-C main bonds are broken to generate free radicals. These free radicals are relatively active and generate peroxide free radicals in the presence of trace oxygen and combine with the composite compatibilizer. The submicron spherical alumina particles are transferred to the composite compatibilizer. Finally, a cross-linked network structure is formed, which greatly improves the dispersibility of the submicron spherical alumina. At the same time, the performance of the waterproof breathable membrane is significantly improved.

[0039] However, excessive addition of submicron spherical alumina, which is dispersed between the flash-evaporated fibers in the waterproof breathable membrane structure, will reduce its air permeability.

[0040] The process of the present application is simple, and the prepared waterproof and breathable membrane has good waterproof and breathable properties, and therefore has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a diagram to compare the effects of different added amounts of composite compatibilizer on the mechanical properties of waterproof breathable membranes. DETAILED DESCRIPTION

[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0043] The following are specific embodiments:

[0044] Example 1

[0045] A waterproof and breathable membrane is made of polyethylene, aluminum oxide and a composite compatibilizer;

[0046] The mass fraction of the aluminum oxide in the waterproof breathable membrane is 0.5%;

[0047] The mass fraction of the composite compatibilizer in the waterproof breathable membrane is 1.2%.

[0048] Alumina is submicron spherical aluminum oxide.

[0049] The particle size of submicron spherical alumina is 0.2 microns.

[0050] The preparation method of the composite compatibilizer is as follows:

[0051] 3 g of maleic acid complex ester and 0.2 g of diisopropylbenzene peroxide were added to 100 mL of organic solvent in sequence, and after stirring and dissolving, 10 g of ethylene-vinyl acetate copolymer was added, and the temperature was adjusted to 70°C, and the mixture was stirred and kept warm for 40 minutes, and then 3 g of polyethylene was added, and the mixture was stirred and kept warm for 2 hours, and then dried by rotary evaporation to obtain a mixture;

[0052] The obtained mixed material is added into a twin-screw extruder for melt extrusion granulation to obtain the compatibilizer.

[0053] The preparation method of maleic acid complex ester is as follows:

[0054] Add sodium silicate to deionized water and stir evenly to obtain a sodium silicate solution with a mass fraction of 6%;

[0055] Add 8% ammonium nitrate solution by mass to the sodium silicate solution until the pH of the mixed solution reaches 10, stop adding the ammonium nitrate solution, place it in a water bath at 75°C for aging for 2 hours, filter it, wash it until it is neutral, dry it for 20 hours, grind it, and sieve it to obtain a support;

[0056] Heat 100 mL of deionized water to 80° C., then add 6 g of zirconium sulfate, stir evenly, then add 15 g of the support, continue stirring for 30 min, then evaporate the water to obtain a reaction material, place the reaction material in a resistance furnace, calcine for 40 min, and naturally cool to room temperature to obtain a composite catalyst;

[0057] 20 g of maleic acid and 28 g of n-butanol were added to 120 mL of toluene, and then 3 g of a composite catalyst was added. After reflux reaction for 3 hours, the solvent was removed by vacuum distillation to obtain a maleic acid composite ester.

[0058] The organic solvent is acetone.

[0059] The extrusion temperature of the twin-screw extruder is 165°C;

[0060] The screw speed is 50r / min.

[0061] A method for processing a waterproof breathable membrane comprises the following steps:

[0062] (1) Processing of spinning solution

[0063] Dissolving the spinning raw materials polyethylene, aluminum oxide and a composite compatibilizer in a spinning solvent in sequence to obtain a spinning solution;

[0064] The mass fraction of spinning raw materials in the spinning solution is 7%;

[0065] (2) Processing of waterproof and breathable membrane

[0066] The spinning solution prepared in step (1) is flash-spun at 190° C. to obtain flash-spun fibers, which are then laid onto a web, subjected to a heat pressing process and a calendering process, and finally wound to obtain a waterproof and breathable membrane.

[0067] The spinning solvent is selected from one or more combinations of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, unsaturated hydrocarbons, halogenated hydrocarbons, alcohols, esters, ethers, and fluorocarbons;

[0068] The temperature of the hot pressing process is 105°C;

[0069] The temperature of the calendering process was 110°C.

[0070] Example 2

[0071] A waterproof and breathable membrane is made of polyethylene, aluminum oxide and a composite compatibilizer;

[0072] The mass fraction of the aluminum oxide in the waterproof breathable membrane is 0.8%;

[0073] The mass fraction of the composite compatibilizer in the waterproof breathable membrane is 1.5%.

[0074] Alumina is submicron spherical aluminum oxide.

[0075] The particle size of submicron spherical alumina is 0.5 micron.

[0076] The preparation method of the composite compatibilizer is as follows:

[0077] 4 g of maleic acid complex ester and 0.3 g of dicumyl peroxide were added to 102 mL of organic solvent in sequence, and after stirring and dissolving, 11 g of ethylene-vinyl acetate copolymer was added to adjust the temperature to 72°C, and the mixture was stirred and kept warm for 40 minutes, and then 5 g of polyethylene was added, and the mixture was stirred and kept warm for 2.5 hours, and then dried by rotary evaporation to obtain a mixture;

[0078] The obtained mixed material is added into a twin-screw extruder for melt extrusion granulation to obtain the compatibilizer.

[0079] The preparation method of maleic acid complex ester is as follows:

[0080] Add sodium silicate to deionized water and stir evenly to obtain a sodium silicate solution with a mass fraction of 6.5%;

[0081] Add 8% ammonium nitrate solution by mass to the sodium silicate solution until the pH of the mixed solution reaches 10, stop adding the ammonium nitrate solution, place it in a water bath at 75°C for aging for 2 hours, filter it, wash it until it is neutral, dry it for 20 hours, grind it, and sieve it to obtain a support;

[0082] 100 mL of deionized water was heated to 80° C., and then 6.4 g of zirconium sulfate was added, and after stirring evenly, 16 g of the support was added, and stirring was continued for 30 min, and then the water was evaporated to dryness to obtain a reaction material, and the reaction material was placed in a resistance furnace and calcined for 40 min, and naturally cooled to room temperature to obtain a composite catalyst;

[0083] 21 g of maleic acid and 29 g of n-butanol were added to 120 mL of toluene, and 3.5 g of a composite catalyst was added. After reflux reaction for 3 hours, the solvent was removed by vacuum distillation to obtain a maleic acid composite ester.

[0084] The organic solvent is acetone.

[0085] The extrusion temperature of the twin-screw extruder is 168°C;

[0086] The screw speed is 50r / min.

[0087] A method for processing a waterproof breathable membrane comprises the following steps:

[0088] (1) Processing of spinning solution

[0089] Dissolving the spinning raw materials polyethylene, aluminum oxide and a composite compatibilizer in a spinning solvent in sequence to obtain a spinning solution;

[0090] The mass fraction of spinning raw materials in the spinning solution is 12%;

[0091] (2) Processing of waterproof and breathable membrane

[0092] The spinning solution prepared in step (1) is flash-spun at 200° C. to obtain flash-spun fibers, which are then laid onto a web, subjected to a heat pressing process and a calendering process, and finally wound to obtain a waterproof and breathable membrane.

[0093] The spinning solvent is selected from one or more combinations of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, unsaturated hydrocarbons, halogenated hydrocarbons, alcohols, esters, ethers, and fluorocarbons;

[0094] The temperature of the hot pressing process is 108°C;

[0095] The temperature of the calendering process was 114°C.

[0096] Example 3

[0097] A waterproof and breathable membrane is made of polyethylene, aluminum oxide and a composite compatibilizer;

[0098] The mass fraction of the aluminum oxide in the waterproof breathable membrane is 1%;

[0099] The mass fraction of the composite compatibilizer in the waterproof breathable membrane is 1.8%.

[0100] Alumina is submicron spherical aluminum oxide.

[0101] The particle size of submicron spherical alumina is 1 micron.

[0102] The preparation method of the composite compatibilizer is as follows:

[0103] 5 g of maleic acid complex ester and 0.4 g of diisopropylbenzene peroxide were added to 110 mL of organic solvent in sequence, and after stirring and dissolving, 14 g of ethylene-vinyl acetate copolymer was added to adjust the temperature to 75°C, and the mixture was stirred and kept warm for 40 minutes, and then 6 g of polyethylene was added, and the mixture was stirred and kept warm for 3 hours, and then dried by rotary evaporation to obtain a mixture;

[0104] The obtained mixed material is added into a twin-screw extruder for melt extrusion granulation to obtain the compatibilizer.

[0105] The preparation method of maleic acid complex ester is as follows:

[0106] Add sodium silicate to deionized water and stir evenly to obtain a sodium silicate solution with a mass fraction of 7%;

[0107] Add 8% ammonium nitrate solution by mass to the sodium silicate solution until the pH of the mixed solution reaches 10, stop adding the ammonium nitrate solution, place it in a water bath at 75°C for aging for 2 hours, filter it, wash it until it is neutral, dry it for 20 hours, grind it, and sieve it to obtain a support;

[0108] 100 mL of deionized water was heated to 80° C., and then 7 g of zirconium sulfate was added, and after stirring evenly, 18 g of the support was added, and stirring was continued for 30 min, and then the water was evaporated to obtain a reaction material, and the reaction material was placed in a resistance furnace and calcined for 40 min, and naturally cooled to room temperature to obtain a composite catalyst;

[0109] 23 g of maleic acid and 30 g of n-butanol were added to 120 mL of toluene, and 4 g of a composite catalyst was added. After reflux reaction for 3 hours, the solvent was removed by vacuum distillation to obtain a maleic acid composite ester.

[0110] The organic solvent is acetone.

[0111] The extrusion temperature of the twin-screw extruder is 170°C;

[0112] The screw speed is 50r / min.

[0113] A method for processing a waterproof breathable membrane comprises the following steps:

[0114] (1) Processing of spinning solution

[0115] Dissolving the spinning raw materials polyethylene, aluminum oxide and a composite compatibilizer in a spinning solvent in sequence to obtain a spinning solution;

[0116] The mass fraction of spinning raw materials in the spinning solution is 7-16%;

[0117] (2) Processing of waterproof and breathable membrane

[0118] The spinning solution prepared in step (1) is flash-spun at 220° C. to obtain flash-spun fibers, which are then laid onto a web, subjected to a heat pressing process and a calendering process, and finally wound to obtain a waterproof and breathable membrane.

[0119] The spinning solvent is selected from one or more combinations of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, unsaturated hydrocarbons, halogenated hydrocarbons, alcohols, esters, ethers, and fluorocarbons;

[0120] The temperature of the hot pressing process is 110°C;

[0121] The temperature of the calendering process was 120°C.

[0122] Comparative Example 1

[0123] A waterproof and breathable membrane is made of polyethylene, aluminum oxide and a composite compatibilizer;

[0124] The mass fraction of the aluminum oxide in the waterproof breathable membrane is 0.25%;

[0125] The mass fraction of the composite compatibilizer in the waterproof breathable membrane is 1.2%.

[0126] Alumina is submicron spherical aluminum oxide.

[0127] The particle size of submicron spherical alumina is 0.2 microns.

[0128] The preparation method of the composite compatibilizer is as follows:

[0129] 3 g of maleic acid complex ester and 0.2 g of diisopropylbenzene peroxide were added to 100 mL of organic solvent in sequence, and after stirring and dissolving, 10 g of ethylene-vinyl acetate copolymer was added, and the temperature was adjusted to 70°C, and the mixture was stirred and kept warm for 40 minutes, and then 3 g of polyethylene was added, and the mixture was stirred and kept warm for 2 hours, and then dried by rotary evaporation to obtain a mixture;

[0130] The obtained mixed material is added into a twin-screw extruder for melt extrusion granulation to obtain the compatibilizer.

[0131] The preparation method of maleic acid complex ester is as follows:

[0132] Add sodium silicate to deionized water and stir evenly to obtain a sodium silicate solution with a mass fraction of 6%;

[0133] Add 8% ammonium nitrate solution by mass to the sodium silicate solution until the pH of the mixed solution reaches 10, stop adding the ammonium nitrate solution, place it in a water bath at 75°C for aging for 2 hours, filter it, wash it until it is neutral, dry it for 20 hours, grind it, and sieve it to obtain a support;

[0134] Heat 100 mL of deionized water to 80° C., then add 6 g of zirconium sulfate, stir evenly, then add 15 g of the support, continue stirring for 30 min, then evaporate the water to obtain a reaction material, place the reaction material in a resistance furnace, calcine for 40 min, and naturally cool to room temperature to obtain a composite catalyst;

[0135] 20 g of maleic acid and 28 g of n-butanol were added to 120 mL of toluene, and then 3 g of a composite catalyst was added. After reflux reaction for 3 hours, the solvent was removed by vacuum distillation to obtain a maleic acid composite ester.

[0136] The organic solvent is acetone.

[0137] The extrusion temperature of the twin-screw extruder is 165°C;

[0138] The screw speed is 50r / min.

[0139] A method for processing a waterproof breathable membrane comprises the following steps:

[0140] (1) Processing of spinning solution

[0141] Dissolving the spinning raw materials polyethylene, aluminum oxide and a composite compatibilizer in a spinning solvent in sequence to obtain a spinning solution;

[0142] The mass fraction of spinning raw materials in the spinning solution is 7%;

[0143] (2) Processing of waterproof and breathable membrane

[0144] The spinning solution prepared in step (1) is flash-spun at 190° C. to obtain flash-spun fibers, which are then laid onto a web, subjected to a heat pressing process and a calendering process, and finally wound to obtain a waterproof and breathable membrane.

[0145] The spinning solvent is selected from one or more combinations of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, unsaturated hydrocarbons, halogenated hydrocarbons, alcohols, esters, ethers, and fluorocarbons;

[0146] The temperature of the hot pressing process is 105°C;

[0147] The temperature of the calendering process was 110°C.

[0148] Comparative Example 2

[0149] A waterproof and breathable membrane is made of polyethylene, aluminum oxide and a composite compatibilizer;

[0150] The mass fraction of the aluminum oxide in the waterproof breathable membrane is 1.25%;

[0151] The mass fraction of the composite compatibilizer in the waterproof breathable membrane is 1.2%.

[0152] Alumina is submicron spherical aluminum oxide.

[0153] The particle size of submicron spherical alumina is 0.2 microns.

[0154] The preparation method of the composite compatibilizer is as follows:

[0155] 3 g of maleic acid complex ester and 0.2 g of diisopropylbenzene peroxide were added to 100 mL of organic solvent in sequence, and after stirring and dissolving, 10 g of ethylene-vinyl acetate copolymer was added, and the temperature was adjusted to 70°C, and the mixture was stirred and kept warm for 40 minutes, and then 3 g of polyethylene was added, and the mixture was stirred and kept warm for 2 hours, and then dried by rotary evaporation to obtain a mixture;

[0156] The obtained mixed material is added into a twin-screw extruder for melt extrusion granulation to obtain the compatibilizer.

[0157] The preparation method of maleic acid complex ester is as follows:

[0158] Add sodium silicate to deionized water and stir evenly to obtain a sodium silicate solution with a mass fraction of 6%;

[0159] Add 8% ammonium nitrate solution by mass to the sodium silicate solution until the pH of the mixed solution reaches 10, stop adding the ammonium nitrate solution, place it in a water bath at 75°C for aging for 2 hours, filter it, wash it until it is neutral, dry it for 20 hours, grind it, and sieve it to obtain a support;

[0160] Heat 100 mL of deionized water to 80° C., then add 6 g of zirconium sulfate, stir evenly, then add 15 g of the support, continue stirring for 30 min, then evaporate the water to obtain a reaction material, place the reaction material in a resistance furnace, calcine for 40 min, and naturally cool to room temperature to obtain a composite catalyst;

[0161] 20 g of maleic acid and 28 g of n-butanol were added to 120 mL of toluene, and then 3 g of a composite catalyst was added. After reflux reaction for 3 hours, the solvent was removed by vacuum distillation to obtain a maleic acid composite ester.

[0162] The organic solvent is acetone.

[0163] The extrusion temperature of the twin-screw extruder is 165°C;

[0164] The screw speed is 50r / min.

[0165] A method for processing a waterproof breathable membrane comprises the following steps:

[0166] (1) Processing of spinning solution

[0167] Dissolving the spinning raw materials polyethylene, aluminum oxide and a composite compatibilizer in a spinning solvent in sequence to obtain a spinning solution;

[0168] The mass fraction of spinning raw materials in the spinning solution is 7%;

[0169] (2) Processing of waterproof and breathable membrane

[0170] The spinning solution prepared in step (1) is flash-spun at 190° C. to obtain flash-spun fibers, which are then laid onto a web, subjected to a heat pressing process and a calendering process, and finally wound to obtain a waterproof and breathable membrane.

[0171] The spinning solvent is selected from one or more combinations of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, unsaturated hydrocarbons, halogenated hydrocarbons, alcohols, esters, ethers, and fluorocarbons;

[0172] The temperature of the hot pressing process is 105°C;

[0173] The temperature of the calendering process was 110°C.

[0174] Comparative Example 3

[0175] A waterproof and breathable membrane is made of polyethylene, aluminum oxide and a composite compatibilizer;

[0176] The mass fraction of the aluminum oxide in the waterproof breathable membrane is 1.5%;

[0177] The mass fraction of the composite compatibilizer in the waterproof breathable membrane is 1.2%.

[0178] Alumina is submicron spherical aluminum oxide.

[0179] The particle size of submicron spherical alumina is 0.2 microns.

[0180] The preparation method of the composite compatibilizer is as follows:

[0181] 3 g of maleic acid complex ester and 0.2 g of diisopropylbenzene peroxide were added to 100 mL of organic solvent in sequence, and after stirring and dissolving, 10 g of ethylene-vinyl acetate copolymer was added, and the temperature was adjusted to 70°C, and the mixture was stirred and kept warm for 40 minutes, and then 3 g of polyethylene was added, and the mixture was stirred and kept warm for 2 hours, and then dried by rotary evaporation to obtain a mixture;

[0182] The obtained mixed material is added into a twin-screw extruder for melt extrusion granulation to obtain the compatibilizer.

[0183] The preparation method of maleic acid complex ester is as follows:

[0184] Add sodium silicate to deionized water and stir evenly to obtain a sodium silicate solution with a mass fraction of 6%;

[0185] Add 8% ammonium nitrate solution by mass to the sodium silicate solution until the pH of the mixed solution reaches 10, stop adding the ammonium nitrate solution, place it in a water bath at 75°C for aging for 2 hours, filter it, wash it until it is neutral, dry it for 20 hours, grind it, and sieve it to obtain a support;

[0186] Heat 100 mL of deionized water to 80° C., then add 6 g of zirconium sulfate, stir evenly, then add 15 g of the support, continue stirring for 30 min, then evaporate the water to obtain a reaction material, place the reaction material in a resistance furnace, calcine for 40 min, and naturally cool to room temperature to obtain a composite catalyst;

[0187] 20 g of maleic acid and 28 g of n-butanol were added to 120 mL of toluene, and then 3 g of a composite catalyst was added. After reflux reaction for 3 hours, the solvent was removed by vacuum distillation to obtain a maleic acid composite ester.

[0188] The organic solvent is acetone.

[0189] The extrusion temperature of the twin-screw extruder is 165°C;

[0190] The screw speed is 50r / min.

[0191] A method for processing a waterproof breathable membrane comprises the following steps:

[0192] (1) Processing of spinning solution

[0193] Dissolving the spinning raw materials polyethylene, aluminum oxide and a composite compatibilizer in a spinning solvent in sequence to obtain a spinning solution;

[0194] The mass fraction of spinning raw materials in the spinning solution is 7%;

[0195] (2) Processing of waterproof and breathable membrane

[0196] The spinning solution prepared in step (1) is flash-spun at 190° C. to obtain flash-spun fibers, which are then laid onto a web, subjected to a heat pressing process and a calendering process, and finally wound to obtain a waterproof and breathable membrane.

[0197] The spinning solvent is selected from one or more combinations of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, unsaturated hydrocarbons, halogenated hydrocarbons, alcohols, esters, ethers, and fluorocarbons;

[0198] The temperature of the hot pressing process is 105°C;

[0199] The temperature of the calendering process was 110°C.

[0200] Comparative Example 4

[0201] A waterproof and breathable membrane is made of polyethylene, aluminum oxide and a composite compatibilizer;

[0202] The mass fraction of the aluminum oxide in the waterproof breathable membrane is 1.75%;

[0203] The mass fraction of the composite compatibilizer in the waterproof breathable membrane is 1.2%.

[0204] Alumina is submicron spherical aluminum oxide.

[0205] The particle size of submicron spherical alumina is 0.2 microns.

[0206] The preparation method of the composite compatibilizer is as follows:

[0207] 3 g of maleic acid complex ester and 0.2 g of diisopropylbenzene peroxide were added to 100 mL of organic solvent in sequence, and after stirring and dissolving, 10 g of ethylene-vinyl acetate copolymer was added, and the temperature was adjusted to 70°C, and the mixture was stirred and kept warm for 40 minutes, and then 3 g of polyethylene was added, and the mixture was stirred and kept warm for 2 hours, and then dried by rotary evaporation to obtain a mixture;

[0208] The obtained mixed material is added into a twin-screw extruder for melt extrusion granulation to obtain the compatibilizer.

[0209] The preparation method of maleic acid complex ester is as follows:

[0210] Add sodium silicate to deionized water and stir evenly to obtain a sodium silicate solution with a mass fraction of 6%;

[0211] Add 8% ammonium nitrate solution by mass to the sodium silicate solution until the pH of the mixed solution reaches 10, stop adding the ammonium nitrate solution, place it in a water bath at 75°C for aging for 2 hours, filter it, wash it until it is neutral, dry it for 20 hours, grind it, and sieve it to obtain a support;

[0212] Heat 100 mL of deionized water to 80° C., then add 6 g of zirconium sulfate, stir evenly, then add 15 g of the support, continue stirring for 30 min, then evaporate the water to obtain a reaction material, place the reaction material in a resistance furnace, calcine for 40 min, and naturally cool to room temperature to obtain a composite catalyst;

[0213] 20 g of maleic acid and 28 g of n-butanol were added to 120 mL of toluene, and then 3 g of a composite catalyst was added. After reflux reaction for 3 hours, the solvent was removed by vacuum distillation to obtain a maleic acid composite ester.

[0214] The organic solvent is acetone.

[0215] The extrusion temperature of the twin-screw extruder is 165°C;

[0216] The screw speed is 50r / min.

[0217] A method for processing a waterproof breathable membrane comprises the following steps:

[0218] (1) Processing of spinning solution

[0219] Dissolving the spinning raw materials polyethylene, aluminum oxide and a composite compatibilizer in a spinning solvent in sequence to obtain a spinning solution;

[0220] The mass fraction of spinning raw materials in the spinning solution is 7%;

[0221] (2) Processing of waterproof and breathable membrane

[0222] The spinning solution prepared in step (1) is flash-spun at 190° C. to obtain flash-spun fibers, which are then laid onto a web, subjected to a heat pressing process and a calendering process, and finally wound to obtain a waterproof and breathable membrane.

[0223] The spinning solvent is selected from one or more combinations of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, unsaturated hydrocarbons, halogenated hydrocarbons, alcohols, esters, ethers, and fluorocarbons;

[0224] The temperature of the hot pressing process is 105°C;

[0225] The temperature of the calendering process was 110°C.

[0226] test:

[0227] Test parameters, methods and standards:

[0228] 1 Hydrostatic pressure test standard AATCC TM127-2017 (2018), water pressure acceleration is 60mbar / min, distilled water temperature is 21℃;

[0229] 2 The test standard for Gurley air permeability resistance is GBT 458-2008 Determination of air permeability of paper and paperboard, that is, the time taken for 100 ml of gas to pass through the test sample;

[0230] 3 Mechanical properties are tested according to GB / 1040-2006 standard;

[0231] Table 1

[0232]

[0233] It can be seen from Table 1 that with the increase in the amount of submicron spherical alumina added, the hydrostatic pressure of the waterproof breathable membrane increases, but the air permeability continues to weaken. In the proportion range of 0.5-1%, the waterproof breathable membrane has more suitable waterproof and breathable performance.

[0234] Taking Example 1 as the basic sample, the effects of different composite compatibilizers on the hydrostatic pressure of the waterproof breathable membrane are compared:

[0235] Table 2

[0236] Composite compatibilizer% <![CDATA[Hydrostatic pressure cmH2O]]> 0 180 0.4 186 0.8 193 1.2 203 1.6 214 2.0 200

[0237] It can be seen from Table 2 that the present invention can improve and increase the hydrostatic pressure of the waterproof breathable membrane by introducing a certain amount of composite compatibilizer.

[0238] Based on the sample of Example 1, the effects of different addition amounts of the composite compatibilizer on the mechanical properties of the waterproof breathable membrane were compared. Figure 1 .

[0239] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A waterproof breathable membrane, characterized in that: Made of polyethylene, alumina and composite compatibilizer; The mass fraction of the aluminum oxide in the waterproof breathable membrane is 0.5-1%; The mass fraction of the composite compatibilizer in the waterproof breathable membrane is 1.2-1.8%; the alumina is submicron spherical alumina; the particle size of the submicron spherical alumina is 0.2-1 micron; the preparation method of the composite compatibilizer is: 3-5g of maleic acid complex ester and 0.2-0.4g of diisopropylbenzene peroxide are added to 100-110mL of organic solvent in sequence, stirred and dissolved, and then 10-14g of ethylene-vinyl acetate copolymer is added to adjust the temperature to 70-75°C, and stirred for 40 minutes, and then 3-6g of polyethylene is added, and the stirring is continued for 2-3 hours, and then the mixture is dried by rotary evaporation to obtain a mixture; The obtained mixed material is added into a twin-screw extruder for melt extrusion granulation to obtain the compatibilizer; the preparation method of the maleic acid complex ester is as follows: Add sodium silicate to deionized water and stir evenly to obtain a sodium silicate solution with a mass fraction of 6-7%; Add 8% ammonium nitrate solution by mass to the sodium silicate solution until the pH of the mixed solution reaches 10, stop adding the ammonium nitrate solution, place it at 75°C, perform water bath insulation aging for 2 hours, filter and wash until neutral, dry it for 20 hours, grind it, and sieve it to obtain a support; Heat 100 mL of deionized water to 80° C., then add 6-7 g of zirconium sulfate, stir evenly, then add 15-18 g of the support, continue stirring for 30 min, then evaporate the water to obtain a reaction material, place the reaction material in a resistance furnace, calcine for 40 min, and naturally cool to room temperature to obtain a composite catalyst; 20-23 g of maleic acid and 28-30 g of n-butanol are added to 120 mL of toluene, and then 3-4 g of a composite catalyst is added. After reflux reaction for 3 hours, the solvent is removed by reduced pressure distillation to obtain a maleic acid composite ester.

2. A waterproof breathable membrane according to claim 1, characterized in that: The organic solvent is acetone.

3. A waterproof breathable membrane according to claim 1, characterized in that: The extrusion temperature of the twin-screw extruder is 165-170°C; The screw speed is 50r / min.

4. The method for processing a waterproof breathable membrane according to claim 1, characterized in that: The following steps are involved: (1) Processing of spinning solution Dissolving the spinning raw materials polyethylene, aluminum oxide and a composite compatibilizer in a spinning solvent in sequence to obtain a spinning solution; The mass fraction of spinning raw materials in the spinning solution is 7-16%; (2) Processing of waterproof and breathable membrane The spinning solution prepared in step (1) is flash-spun at 190-220° C. to obtain flash-spun fibers, which are then laid onto a web, subjected to a heat pressing process and a calendering process, and finally wound to obtain a waterproof and breathable film.

5. The method for processing a waterproof breathable membrane according to claim 4, characterized in that: The spinning solvent is selected from one or more combinations of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, unsaturated hydrocarbons, halogenated hydrocarbons, alcohols, esters, ethers, and fluorocarbons.

6. The method for processing a waterproof breathable membrane according to claim 4, characterized in that: The temperature of the hot pressing process is 105-110°C; The temperature of the calendering process is 110-120°C.

Citation Information

Patent Citations

  • PVC vehicle waterproof film and preparation method thereof

    CN108264700A

  • Microporous filter membrane with both air permeability and barrier property

    CN111408279A

  • Printable polymer sheet and application

    CN115403842A